Interleukin‐15 receptor subunit alpha regulates interleukin‐15 localization and protein expression in skeletal muscle cells. Issue 3 (20th February 2022) - Yoshida, Shino; Fujimoto, Taku; Takahashi, Toshimasa; Sugimoto, Ken; Akasaka, Hiroshi; Tanaka, Minoru; Huang, Yibin; Yasunobe, Yukiko; Xie, Keyu; Ohnishi, Yuri; Minami, Tomohiro; Takami, Yoichi; et al.
Abstract : New Findings: What is the central question of this study? How are the dynamics of interleukin (IL)‐15 and its receptors altered during the differentiation of myoblasts into myotubes, and how is IL‐15 regulated? What is the main finding and its importance? The mRNA levels of IL‐15 and interleukin‐2 receptor subunits beta and gamma increase during skeletal muscle differentiation, whereas interleukin‐15 receptor subunit alpha (IL‐15RA) exhibits different kinetics. IL‐15RA regulates the localization and expression of IL‐15 at the protein level. Abstract: Interleukin‐15 (IL‐15) is a myokine in the interleukin‐2 (IL‐2) family that is generated in the skeletal muscle during exercise. The functional effect of IL‐15 involves muscle regeneration and metabolic regulation in skeletal muscle. Reports have indicated that interleukin‐15 receptor subunit alpha (IL‐15RA) acts by regulating IL‐15 localization in immune cells. However, the dynamics of IL‐15 and its receptors, which regulate the IL‐15 pathway in skeletal muscle differentiation, have not yet been clarified. In this study, we investigated the mechanism of IL‐15 regulation using a mouse skeletal muscle cell line, C2C12 cells. We found that the mRNA expression of IL‐15, interleukin‐2 receptor subunit beta (IL‐2RB; CD122) and interleukin‐2 receptor subunit gamma (IL‐2RG; CD132) increased, but that IL‐15RA exhibited different kinetics as differentiation progressed. We also found that IL‐15, mainly present in the cytosol, pre‐assembled with IL‐15RA in the cytosol and fused to the plasma membrane. Moreover, IL‐15RA increased IL‐15 protein levels. Our findings suggest that genes involved in the IL‐15 signalling complex are enhanced with the differentiation of myotubes and that IL‐15RA regulates the protein kinetics of IL‐15 signalling in skeletal muscle.